Effects of different anesthetic depths monitored by processed EEG analysis on glandular secretion in patients undergoing laparoscopic total hysterectomy - Xia, Ling-yi; Zhang, Qian; Zhuo, Ming; Deng, Zi-hao; Huang, Ke-nv; Zhong, Mao-lin (Frontiers in Anesthesiology, 2023)
Background The objective of this study was to find ways to reduce intraoperative glandular secretion in patients by observing the effects of different depths of anesthesia on glandular secretion under Narcotrend monitoring (NT), to reduce the use of unnecessary anticholinergic drugs, and to improve the quality of anesthesia and patient comfort. Methods Ninety patients who underwent total laparoscopic hysterectomy were randomly divided into three groups. Group L: intraoperative maintenance of anesthesia depth D0–D2, group M: intraoperative maintenance of anesthesia depth E0–E1, group H: long tocopherol 0.01 mg/kg was administered intravenously 10 min before surgery without monitoring the depth of anesthesia, and the mean arterial pressure (MAP), heart rate (HR), and adverse effects were compared in each group at six time points. The salivary secretion and respiratory gland secretion were compared among the groups. Results Salivary secretion under general anesthesia decreased in all three groups compared with the basal value (P < 0.05), with the smallest decrease in group L (P < 0.05) and the largest decrease in group H (P < 0.001). The amount of respiratory gland secretion during the whole operation was from more to less in the order of group L, group M and group H. The dry mouth visual analogue scale (VAS) scores were lower in groups L and M than in group H (P < 0.05). Conclusion General anesthesia suppresses the patient's glandular secretion, and the suppression becomes more pronounced as the anesthesia deepens. Maintaining the depth of anesthesia E0–E1 can effectively reduce the patient's glandular secretion, more stable intraoperative vital signs, and more comfortable patient awakening period without increasing the incidence of adverse reactions. Chinese Clinical Trial Registry http://www.chictr.org.cn/showproj.aspx?proj=147905, identifier ChiCTR2200055422.